2013
DOI: 10.1051/fruits/2012054
|View full text |Cite
|
Sign up to set email alerts
|

A farmer participatory research approach to assess the effectiveness of field sanitation and regular trapping on banana weevil populations

Abstract: A farmer participatory research approach to assess the effectiveness of field sanitation and regular trapping on banana weevil populations.Abstract -Introduction. Small-scale banana producers in Tanzania are facing constraints caused by the destructive activities of the banana weevil (Cosmopolites sordidus Germar). Many currently used methods of addressing the problem are ineffective or too expensive for local farmers to implement. Materials and methods. A combination of two integrated pest management (IPM) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, in an on-station trial, Masanza et al [48] found that crop sanitation reduced C. sordidus adult populations but did not affect damage or yield levels during the duration of the trial. In Tanzania, Rannestad et al [49] found that crop sanitation combined with trapping reduced C. sordidus populations by 33 to 74%. Despite the labor intensity associated with crop sanitation in reduction in the yield loss due to C. sordidus damage, it remains a reliable technology to promote to affect banana farming community.…”
Section: ) Field Sanitationmentioning
confidence: 99%
“…However, in an on-station trial, Masanza et al [48] found that crop sanitation reduced C. sordidus adult populations but did not affect damage or yield levels during the duration of the trial. In Tanzania, Rannestad et al [49] found that crop sanitation combined with trapping reduced C. sordidus populations by 33 to 74%. Despite the labor intensity associated with crop sanitation in reduction in the yield loss due to C. sordidus damage, it remains a reliable technology to promote to affect banana farming community.…”
Section: ) Field Sanitationmentioning
confidence: 99%